What are the consequences of being a downy oak (quercus pubescens) or a holm oak (Q. ilex) for breeding blue tits (Parus caeruleus)? - Blondel, J.; Isenmann, P.; Maistre, M.; Perret, P. (Plant Ecology, 1992)
By comparison with deciduous oaks, the lower yearly production of new leaves in sclerophyllous oaks is hypothesized to have several consequences on animal communities. In particular, the production of arthropod communities that feed upon the leaves should be lower in sclerophyllous than in deciduous oaks, this causing changes in breeding patterns and the demographic balance in insectivorous birds. Studies in both deciduous and sclerophyllous habitats in southern France have shown that: 1) the spring development of new leaves occurs later and more slowly in sclerophyllous than in deciduous oaks, 2) the biomass of caterpillars is much lower in sclerophyllous oak forests, and 3)there is a large variation in life history traits of the Blue Tit depending in which type of habitat they breed. Laying date occurs later and clutch size is lower in sclerophyllous habitats than in deciduous habitats. The evolution of life history traits is discussed according to whether poor sclerophyllous habitats are isolated (e.g. on Corsica) or are parts of landscapes including both habitat types.
Keywords: breeding traits; caterpillars; leafing phenology; Parus caeruleus; Quercus ilex; Quercus pubescens